Multilayered Framework for Mitigating (MLFM) EDoS Attack - Somasundaram, A (International Journal of Computer Sciences and Engineering, 2025)
Cloud Computing” is an attractive model for enterprise businesses because of its on-demand, openness, reduced cost, scalability and pay-by-use business model. The DDoS attack on metered resources of Cloud environment is termed as Fraudulent Resource Consumption (FRC) attack. The FRC Attack leads to EDoS (economic Distributed Denial of Service) attack which aims to consume the cloud resource by attacker and impose financial burden to the legitimate user, where integrity, availability and confidentiality of the cloud services are never compromised but affects the accountability which leads to inaccurate billing. This paper surveys different techniques that generate, detect and mitigate the EDoS Attack on Cloud and proposes a Multilayered Framework for Mitigating EDoS Attack